Differing and isoform-specific roles for the formin DIAPH3 in plasma membrane blebbing and filopodia formation - Št̓astná, Jana; Pan, Xiaoyu; Kutscheidt, Stefan; Lohmann, Volker; Fackler, Oliver Till (Cell research, 2012)
Plasma membrane (PM) blebs are dynamic actin-rich cell protrusions that occur, e.g., during cytokinesis, amoeboid cell motility and cell attachment. Using a targeted siRNA screen against 21 actin nucleation factors, we identify a novel and essential role of the human diaphanous formin DIAPH3 in PM blebbing during cell adhesion. Suppression of DIAPH3 inhibited blebbing to promote rapid cell spreading involving β1-integrin. Multiple isoforms of DIAPH3 were detected on the mRNA and protein level of which isoforms 3 and 7 were the largest and most abundant isoforms that however did not induce formation of actin-rich protrusions. Rather, PM blebbing specifically involved the low abundance isoform 1 of DIAPH3 and activation of isoform 7 by deletion of the diaphanous-autoregulatory domain caused the formation of filopodia. Dimerization and actin assembly activity were essential for induction of specific cell protrusions by DIAPH3 isoforms 1 and 7. Our data suggest that the N-terminal region comprising the GTPase-binding domain determined the subcellular localization of the formin as well as its protrusion activity between blebs and filopodia. We propose that isoform-selective actin assembly by DIAPH3 exerts specific and differentially regulated functions during cell adhesion and motility.